Sports management of indonesian sports athletics preparations in Asian Games 2018 - Lumintuarso, R.; Suharjana; Widiyanto; Ndayisenga, J. (International Journal of Human Movement and Sports Sciences, 2021)
Background: Sport management plays an important role in the athletes' achievement and championship. Sports Management helps us to learn how to overview the business side of sports organization with the use of the latest trends and technologies. Sport management is applied in various fields. The benefit of sport management is to increase the quality of business whether in sport industry, physical education, but it is also used in coaching athletes during the pre-competition, the competition process, and post competition. Purpose: The purpose of this research was to evaluate the principals of sport management like: (1) planning, (2) organizing, (3) staffing, (4) leading and (5) controlling in Asian Games 2018. Design/methodology/approach: This was a qualitative descriptive study. The research sample was made of all Indonesia sports professionals in 2018' games. To collect data, the researcher conducted an assessment of service quality from planning, organizing, staff, leading and control during the Asian championship using questionnaire, interview, and observation. The Results showed that the achievement of the Indonesian athletic team was more programmed and planned, which is evident from the early age athletes were selected and coached by senior athletes. Indonesia's role in the development process was more apparent in the government support, the support of stakeholders, and academics from universities. Conclusion: Sport management is a strong tool that helps physical education teachers, sport medicine managers, and coaching training managers to decide how to improve the peak of performance and to maintain a good quality of athletes and non-athletes.